Artificial Intelligence as a Determinant of Professional Transformation of Real Estate Sector Workers in the Czech Republic in the Early Era of Industry 5.0 - Jaroslav VETESKA; Jaroslav KRIZ (Communications of International Proceedings, 2025)
This study examines the transformation of the professional competencies of real estate sector workers in the Czech Republic in the context of digitalization, the implementation of artificial intelligence, and the emergence of the Industry 5.0 concept, which emphasizes a human-centred approach, sustainability, and cooperation between humans and technology. The aim is to analyse how these processes influence the nature of lifelong professional learning and the development of new metacompetencies in a digitally transformed environment. The research employs a mixed-methods design combining a quantitative questionnaire survey (n = 79) and a qualitative analysis of eight semi-structured interviews. The quantitative data indicated that the greatest use of AI was in text automation, work with visual materials, and document digitalization. The qualitative part identified three competence trajectories: digital adaptability, ethical and decision-making competencies in the context of AI, and complex interdisciplinary learning. The findings confirm a shift from technical skills toward metacompetencies encompassing reflective learning, ethical responsibility, and the ability to collaborate across disciplines. The study emphasizes the need for the concept of Continuing Education 5.0, which develops digital intelligence, ethical culture, and networked collaboration as key elements of sustainability in the real estate sector.
Keywords: artificial intelligence; Industry 5.0; lifelong learning; professional competence transformation; real estate services